DEVELOPMENT OF MONOLOGUE AND DIALOGICAL SPEECH OF STUDENTS OF UNIVERSITIES - Kalmirzaevna , Batirshina Jumakul (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
This article deals with development of monologue and dialogical speech of students of universities. The modern stage of development of the educational process has changed the requirements for the professional training of students. The changes are associated with the development of special disciplines and with the increased role of the Russian language in the conditions of improving the preparation of each student, as this is the key to future success and professionalism.